Antioxidant activity of Crescentia cujete extract: effects on oxidative stress in the hearts of hypoxic rats - David Limanan; Brandon Alexander Setiady; Belinda Sentosa; Alfred H Alphanto; Selly Herlia Rudianti; Frans Ferdinal (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: The heart is highly susceptible to oxidative stress. Hypoxia can induce oxidative stress in the heart, leading to cardiac damage. Objective: This study investigated the antioxidant effects of Crescentia cujete extract on oxidative stress in hypoxic rat hearts. Methods: Antioxidant capacity was evaluated using DPPH assay. Sprague Dawley rats were divided into eight groups: four received C. cujete extract (400 mg/kg/day for 14 days) and four served as controls. Hypoxia was induced for 3, 7, and 14 days using a hypoxic chamber (8% O₂, 92% N₂). Heart tissue was analyzed for malondialdehyde (MDA), glutathione (GSH), and catalase activity. Results: C. cujete extract demonstrated moderate antioxidant capacity (IC50 = 158.45 µg/mL). In extract-treated rats, MDA levels were significantly lower compared to controls, while catalase activity was significantly higher. GSH levels were higher in treated groups but not statistically significant. Histopathological analysis revealed less cardiac necrosis in extract-treated groups. Conclusion: C. cujete extract demonstrates protective effects against hypoxia-induced cardiac oxidative stress. These findings suggest potential as complementary therapy for oxidative cardiac damage, although further studies are needed to establish clinical efficacy and safety.